ホッキョク ニ オケル コタイ チキュウ カガク ケンキュウ ノ ゲンジョウ ト テンボウ ニ カンスル ケンキュウ シュウカイ ホウコク - 金尾, 政紀; カナオ, マサキ; Kanao, Masaki (2005)
P(論文) 平成17年3月23日に国立極地研究所講堂にて,「北極における固体地球科学研究の現状と展望に関する研究集会」が開催された(参加者計19名).最近の北極域での固体地球科学研究に関連する研究者が集まり,研究成果の発表と学際的な情報交換を行い,今後の研究の取り組み方を議論した.最初に,地震計や重力計など近年の観測経過や,わが国の観測拠点であるニーオルスン基地の現状について紹介が行われた.また,北極直下の地球内部の不均質構造やダイナミクスに関する研究発表があり,北極域の観測データを用いた内核最下部マントルの地震学的構造や,氷河の後退に伴う重力値の変動現象について活発な議論が行われた.さらに地球内部を有効に調べるため,グローバル観測網を補う形で北極域のどの場所に新たな観測点を設けるべきか,に関して具体的な意見交換を行った.最後に,シベリアや極東ロシアを中心に,国際極年2007-2008に関連した観測計画の紹介があり,国際共同研究の実際の進め方を議論した. A workshop on Present status and future plans for Solid Earth science in the Arctic region" was held on 23rd March 2005, at the National Institute of Polar Research with 19 participants. The meeting provided the opportunity to review recent Earth Science activities in the Arctic region, followed by a discussion concerning future plans. The first section of the workshop covered the present status of geophysical observations, such as seismic and gravimetric monitoring. Information on scientific investigations and logistic infrastructure of international stations, such as NyAlesund, Svalbard, Norway, was introduced for future utilization by participants. Next, there are several topics concerning heterogeneous structure and dynamics in the interior of the Earth, viewed from the Arctic region. Useful discussions were held involving time variations in gravimetric values associated with Post Glacial Rebound, together with the seismic structure in the depth range between the Inner Core and the Lower-most Mantle. The most suitable geometrical position of new permanent stations in the Arctic region, by taking into consideration the density of seismic ray paths from global teleseismic events was also discussed. Finally, several international cooperative activities are introduced with regard to programs of the International Polar Year (IPY) 2007-2008. departmental bulletin paper